Polymorphisms in TICAM2 and IL1B are associated with TB - Hall, N. B.; Igo Jr., R. P.; Malone, L. L.; Truitt, B.; Schnell, A.; Tao, L.; Okware, B.; Nsereko, M.; Chervenak, K.; Lancioni, C.; Hawn, T. R.; Mayanja-Kizza, H.; et al. (Genes & Immunity, 2015)
Human genetic susceptibility for tuberculosis (TB) has been demonstrated by several studies, but few have examined the multiple innate and adaptive immunity genes comprehensively, age-specific effects and/or resistance to Mycobacterium tuberculosis (Mtb) infection (resistors (RSTRs)). We hypothesized that RSTRs, defined by a persistently negative tuberculin skin test, may have different genetic influences than Mtb disease. We examined 29 candidate genes in pathways that mediate immune responses to Mtb in subjects in a household contact study in Kampala, Uganda. We genotyped 546 haplotype-tagging single-nucleotide polymorphisms (SNPs) in 835 individuals from 481 families; 28.7% had TB, 10.5% were RSTRs, and the remaining 60.8% had latent Mtb infection. Among our most significant findings were SNPs in TICAM2 (P = 3.6 × 10− 6) and IL1B (P = 4.3 × 10− 5) associated with TB. Multiple SNPs in IL4 and TOLLIP were associated with TB (Po0.05). Age–genotype interaction analysis revealed SNPs in IL18 and TLR6 that were suggestively associated with TB in children aged ⩽10 years (P = 2.9 × 10− 3). By contrast, RSTR was associated with SNPs in NOD2, SLC6A3 and TLR4 (nominal Po0.05); these genes were not associated with TB, suggesting distinct genetic influences. We report the first association between TICAM2 polymorphisms and TB and between IL18 and pediatric TB.
Keywords: Polymorphisms; TICAM2; IL1B; TB